Nigeria yearbook 2015 (Nigeria: Industrial Leaders Communications Ltd., 2015)
The yearbook is on issues, people and places in Nigeria; a diary of events in Nigeria and directory.
rua 22/02/17
Ref.
Keywords: Yearbooks; Nigeria